2022
DOI: 10.1186/s12870-022-03461-8
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptome sequencing reveals the molecular mechanism of potato seedlings responding to low-temperature

Abstract: Background Potato (Solanum tuberosum L.) is one of the world's most important crops, the cultivated potato is frost-sensitive, and low-temperature severely influences potato production. However, the mechanism by which potato responds to low-temperature stress is unclear. In this research, we apply a combination of second-generation sequencing and third-generation sequencing technologies to sequence full-length transcriptomes in low-temperature-sensitive cultivars to identify the important genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 117 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…When plants encounter stress, AS can result in a series of defensive stress responses [ 21 ]. Recent studies have revealed that several defence genes undergo alternative splicing that is often affected by pathogen infection [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When plants encounter stress, AS can result in a series of defensive stress responses [ 21 ]. Recent studies have revealed that several defence genes undergo alternative splicing that is often affected by pathogen infection [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, an increasing number of PacBio full-length transcriptome have been sequenced and assembled. These studies have helped us to identify numerous new genes and alternatively spliced isoforms in many species, including potato [ 21 ], sorghum [ 22 ], Larix kaempferi [ 23 ], Italian ryegrass root [ 24 ] and kiwifruit [ 25 ]. Overall, the above studies demonstrated that third-generation sequencing complements second-generation sequencing in the quantitative determination of eukaryotic transcripts and contributes to the discovery of an increasing number of alternatively spliced isoforms [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…TFs bind DNA in a sequence-specific way to control gene transcription ( 73 ). Under stress conditions, organisms activate RNA polymerase II transcription complexes by stimulating TFs through a sequential signal transmission with the appropriate cis-acting element combination, activating the expression of particular genes and response to environmental signals ( 74 , 75 ). Previous studies showed that TFs in association regulated the expression of functionally associated genes under stress conditions, and the overexpression of these TFs either stimulated or suppressed the expression of resistance-related genes to ultimately alter an organism’s capacity to survive in stressed environments ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that TFs in association regulated the expression of functionally associated genes under stress conditions, and the overexpression of these TFs either stimulated or suppressed the expression of resistance-related genes to ultimately alter an organism’s capacity to survive in stressed environments ( 76 ). For example, studies have confirmed that a group of TFs, including bHLH, bZIP, MYB, C2H2, ERF, NAC, and WRKY, play an important role in plant responses to low temperature stress ( 75 ). Our results showed that a total of 1,342 TFs of 43 families were differentially expressed in truffles under cold storage for 0, 15, or 30 d, respectively, with the highest level of abundance of TFs revealed in the C2H2 family, followed by zn-clus, C3H, and bZIP families of TFs.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and content of the extracted DNA and total RNA were checked using a Qubit 2.0 fluorometer (Thermo Fisher Scientific, Waltham, MA, USA) and an Agilent 2100 bioanalyzer (Agilent Technologies, Santa Clara, CA, USA). The genomic short-read library, genomic long-read library, short-read transcriptome library, and full-length transcriptome library were constructed following the standard protocol provided by the sequencer manufacturer and have been ‘described earlier [ 47 , 48 ]. The Hi-C library of R. rosaefolius was constructed following the protocols proposed by Rao et al .…”
Section: Methodsmentioning
confidence: 99%